Mastering Elixir : build and scale concurrent, distributed, and fault-tolerant applications - Albuquerque, André; Caixinha, Daniel (Packt Publishing, 2018)
Running concurrent, fault-tolerant applications that scale is a very demanding responsibility. This book will help you by not only going into detail on several aspects of how Elixir works, but also, and more importantly, will guide you along the way with concrete examples of how to apply the concepts learned to a full-fledged application.